Single‐Junction Organic Photovoltaic Cell with 19% Efficiency. Issue 41 (31st August 2021) - Cui, Yong; Xu, Ye; Yao, Huifeng; Bi, Pengqing; Hong, Ling; Zhang, Jianqi; Zu, Yunfei; Zhang, Tao; Qin, Jinzhao; Ren, Junzhen; Chen, Zhihao; He, Chang; et al.
Abstract: Improving power conversion efficiency (PCE) is important for broadening the applications of organic photovoltaic (OPV) cells. Here, a maximum PCE of 19.0% (certified value of 18.7%) is achieved in single‐junction OPV cells by combining material design with a ternary blending strategy. An active layer comprising a new wide‐bandgap polymer donor named PBQx‐TF and a new low‐bandgap non‐fullerene acceptor (NFA) named eC9‐2Cl is rationally designed. With optimized light utilization, the resulting binary cell exhibits a good PCE of 17.7%. An NFA F‐BTA3 is then added to the active layer as a third component to simultaneously improve the photovoltaic parameters. The improved light unitization, cascaded energy level alignment, and enhanced intermolecular packing result in open‐circuit voltage of 0.879 V, short‐circuit current density of 26.7 mA cm −2, and fill factor of 0.809. This study demonstrates that further improvement of PCEs of high‐performance OPV cells requires fine tuning of the electronic structures and morphologies of the active layers. Abstract : By designing new donor/acceptor materials and combining a ternary blending strategy, a maximum power conversion efficiency (PCE) of 19.0% (certified value of 18.7%) in single‐junction organic photovoltaic (OPV) cells is achieved. It is demonstrated that finely tuning the light utilization and photophysical processes of the active layer has great potential for further improving the PCEs of OPV cells.